Consider the costs of student attrition. Issue 6 (September 2015) - Marthers, Paul; Herrup, Peter; Steele, Jonathan
<x xml:space="preserve">Abstract</x> Efficient enrollment management offices routinely calculate the return on the investment made in recruitment, yield and retention activities. Offices track cost per applicant, cost per enrollee, net tuition revenue, etc. There are national benchmarks for such performance data. For example, the median cost to recruit a student is 2, 433 for private colleges and 457 for public colleges, according to research published by Ruffalo Noel Levitz (see<ext-link ext-link-type="uri" xlink:href="https://www.noellevitz.com/papers-research-higher-education/2013/2013-cost-of-recruiting-an-undergraduate-student-report" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">https://www.noellevitz.com/papers‐research‐higher‐education/2013/2013‐cost‐of‐recruiting‐an‐undergraduate‐student‐report).